Comparison of Clinical, Hematological and Bacteriological Profile of Neonatal Sepsis between Term and Preterm Babies (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Neonatal sepsis is an important public health problem with a high morbidity and mortality. Globally, it has been reported that preterm newborns have a 13 times greater risk of death than full term newborn babies. Clinical, hematological parameters and the spectrum of organisms causing neonatal sepsis may vary between term and preterm. Present study is a good opportunity to evaluate clinical, haematological & bacteriological profile of neonatal sepsis in preterm & term.Materials and methods: This hospital based observational and comparative study was carried out in Special Care Newborn Unit (SCANU) of Chittagong Medical College Hospital where a total of 100 clinically suspected neonatal sepsis cases was enrolled, out of which 50 were preterm and 50 term neonates. Clinical, hematological and bacteriological profiles were compared between two groups.Results: Hypothermia was an important clinical feature occurring in 70.0% preterm and 16.0% term cases. Mean platelet count was 1.04±0.73 lacs/cmm in preterm and 1.52±0.78 lacs/cmm in term cases. In term and preterm neonates CRP were observed to be 39.42±32.99mg/L and 26.20±22.25 mg/L (p=0.021). Klebsiella species was the predominant isolated bacteria in both groups, showing 16.0% in preterm and 14.0% in term cases, followed by S. aureus, Acinetobacter species and Candida species.Conclusion: Neonatal sepsis is an important cause of morbidity and mortality. There is need of large scale studies, in hope of developing a better prevention policy in both term and preterm babies.JCMCTA 2021 ; 32 (1) : 21-25